An Assessment of College Students’ Use of Social Media for Agriculture-related Information Seeking - Enoch Teye Kwao Ametepey; Casandra K Cox Dr.; Kobina Danful Fanyinkah; Grace Vehige (Journal of Applied Communications, 2025)
The purpose of this study was to assess college student's use of social media for agriculture-related information seeking. The study was guided by the Media Dependency Theory. A quantitative descriptive research design was used to elicit data from undergraduate college students enrolled in a junior-level communicating agriculture to the public class. Results revealed college students frequently obtain their agriculture-related news and information from news websites/apps and social media. Instagram was found to be the top social media platform used by respondents for seeking agriculture-related information, with a majority using it daily. Instagram was the most used followed by YouTube, Facebook, TikTok, and X. Furthermore, the study found while undergraduate students frequently engaged with digital content, their use of social media for agriculture-specific information was less pronounced. Respondents utilized social media for agriculture-related entertainment, national news on agriculture-related topics occasionally, and international agriculture-related information less frequently. Future studies should explore the key social media influencers in agriculture, the role of social media influencers in shaping perceptions of agricultural content, the effectiveness of different types of content, and the integration of social media within professional agricultural networks. The evolving role of social media in agricultural communications presents both challenges and opportunities. However, integrating social media into educational frameworks and understanding the preferences of students can foster a more engaged and informed generation.
Keywords: social media; agriculture-related information; Media Dependency Theory; college students.